Climate Change on Agency Practices of Fisherwives Based on Sustainable Livelihood in Coastal Communities - Oktavia Ningrum (Universitas Sebelas Maret (UNS), 2025)
Climate change is increasingly widespread and affects the sustainability of human life, as well as fishermen's households in Bantan Tengah Village, Bantan District, Bengkalis Regency, Riau, which feel significant impacts in coastal areas. On the one hand, fishing households have been closely associated with economic uncertainty. Therefore, to save life and adapt the role of a wife is needed. This is done by applying agency through ways or creative ideas of a fisherman's wife who utilizes existing resources around her environment. In line with this, this research aims to find out how the ecological dynamics of coastal communities as a result of climate change and the practice of women's agency in dealing with the impacts of climate change based on sustainable livelihood in coastal communities. This research was carried out by applying a qualitative method along with a phenomenological approach. Data sources come from primary and secondary sources. Data completeness is obtained through primary data such as interviews, observations, and documentation. In addition, secondary data utilized scientific writings such as books, journals, literature analysis, government policies, theses, scientific articles, and news obtained online related to the research. In determining informants, this research uses purposive sampling. Pierre Bourdieu's Social Practice Theory was chosen in this research to see and analyze this phenomenon. This research shows that fishermen experience the impact of climate change in the form of wind and wind speed that affects waves and currents, pollution through dirty water, the emergence of a lot of garbage, changes and limited fishing ground areas, and reduced fish catches. This causes fishermen's wives to carry out agency in the form of creating strategies for buying and selling fish catches, diversifying the processing of fish catches, building strategies to maintain the quality of mangrove charcoal, hunting areca nuts in Javanese, and fishing under mangrove trees. All agencies are carried out by utilizing supporting factors in the economic, social, and cultural aspects to be able to achieve sustainable livelihood. Thus, through the generative formula of social practices generated from habitus, capital, and domain, fishermen households are able to get a sustainable life or called sustainable livelihood.